Adsorption of Aqueous Mercury(II) Species by Commercial Activated Carbon Fibres with and without Surface Modification - João M. Valente Nabais; Peter J.M. Carrott; Manuela Ribeiro Carrott; Sara Silvestre; Carlos J. Durán-Valle (Adsorption Science & Technology)
The adsorption of HgCl 2 , [HgCl 4 ] 2– and Hg 2+ onto a series of activated carbon fibres was studied. These included the as-received commercial activated carbon fibre (K), that obtained after modification via by sulphuric acid oxidation (K AC ) and that obtained after modification by reaction with pentaethylenehexamine (K BAS ). The effects of concentration (10–1500 mg/l), solution pH (1–10) and temperature (25°C, 35°C and 45°C) were studied. The mercury(II) adsorption isotherms followed the Langmuir model with maximum adsorption capacities of 361.0, 142.2 and 300.3 mg/g for HgCl 2 , [HgCl 4 ] 2– and Hg 2+ , respectively. Fibre K proved to have the highest adsorption capacity towards HgCl 2 but the best results for the adsorption of [HgCl 4 ] 2– and Hg 2+ were obtained with the fibre K AC . The performance of fibre K BAS was always worse than those of the other two fibres tested. The negative values obtained for ΔH 0 and ΔG 0 indicate that the adsorption was an exothermic and spontaneous process and also demonstrated that the adsorption of Hg(II) is a feasible process.